Mengembalikan Fungsi Kognisi Pasien Penyakit Jantung di RSI Sunan Kudus Melalui Layanan Bimbingan Islam - Susana Aditiya Wangsanata; Ali Murtadho; Ema Hidayanti (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This study aims to describe Islamic guidance services in improving the cognitive function of heart disease patients at Sunan Kudus Hospital. The data source of this study were clergy and heart disease patients at Sunan Kudus Hospital. Data collected by observation, interview and documentation. Data analysis using Miles and Huberman's theory, began the collection, presentation, and inference of data. The results of this study indicate that heart disease patients at Sunan Kudus Hospital have a negative cognitive function that is the mind focuses on pain and death. The practice of Islamic guidance in improving the cognitive function of heart disease patients uses the direct method of visiting clergy in each patient's room. The indirect method is by using Qur'anic healing, namely by listening to verses of the Qur'an to the patient through the speaker. This guidance practice provides positive benefits to the cognitive function of the patient. This positive benefit is seen in the attention, memory and ways of solving the patient's problem. Patient's attention is no longer too focused on pain and death. Meanwhile the patient's memory by remembering Allah Almighty the mind becomes more calm, and the patient is able to find solutions to the problems being faced.